Impactos do IFRS nas atividades de hedge das empresas: evidências para o mercado brasileiro - Carvalho, Rafael Rodrigues (2014)
This study aims to analyze possible changes in the use and accounting of derivatives depending on the convergence of Brazilian accounting standards to international standards (IFRS - IAS 39). The research is based on non-financial Brazilian companies and use as information explanatory notes regarding derivatives and the volatility of selected balance sheet accounts: earnings and cash flows. Despite the assumptions made, the results showed that the change in accounting standards did not affect the use of derivatives and, also, it was not found any evidence about the impact on the volatility of cash flow and net income. Finally, it was observed that the alternative method for hedge accounting softened the volatility of the firm's profits.